Modelling modal-split and trip length in a simultaneously discrete-continuous setting - Rich, Jeppe Husted (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Econometrics models for traffic behaviour as modal-split, car ownership, travel purpose, etc. is often based on the assumption that individual behaviour can be decomposed into a finite set of discrete choice. However, in some circumstances, for instance in modelling actual demand measured as trip length, this approach fails to fit reality. This paper present a simultaneous model set-up for the joint decision of modal-split and trip length being continuous. The model is estimated in a general maximum likelihood framework and is based on a stratified sample for Aarhus, the second largest city in Denmark.